Copper-Catalyzed Electrophilic Amination of Organoboron Compounds - Lalic, Gojko; Rucker, Richard P. (Synlett, 2013)
A new procedure for direct transformation of alkenes to tertiary alkylamines based on hydroboration and copper-catalyzed amination of alkylboranes is described. The new method is presented in a broader context provided by a brief analysis of various approaches to the formation of anti-Markovnikov hydroamination products. A short discussion of the reaction development, scope, and the mechanism are also provided. Finally, the extension of this methodology to the preparation of hindered anilines from aryl boronic esters is presented.
Keywords: organoboron compounds; hydroamination; transition metals; catalysis; electrophilic amination